Role of Sphingosine Kinase 1 and Sphingosine-1-Phosphate Axis in Hepatocellular Carcinoma - Maceyka, Michael (Handb Exp Pharmacol, 2020)
Hepatocellular carcinoma (HCC) is primarily diagnosed in the latter stages of disease progression and is the third leading cause of cancer deaths worldwide. Thus, there is a need to find biomarkers of early HCC as well as the development of more effective treatments for the disease. Sphingosine-1-phosphate (S1P) is a pleiotropic lipid signaling molecule produced by two isoforms of sphingosine kinase (SphK1 and SphK2) that is involved in regulation of many aspects of mammalian physiology and pathophysiology, including inflammation, epithelial and endothelial barrier function, cancer, and metastasis, among many others. Abundant evidence indicates that SphK1 and S1P promote cancer progression and metastasis in multiple types of cancers. However, the role of SphK/S1P in HCC is less well studied. Here, we review the current state of knowledge of SphKs and S1P in HCC, including evidence for the correlation of SphK1 expression and S1P levels with progression of HCC and negative outcomes, and discuss how this information could lead to the design of more effective diagnostic and treatment modalities for HCC.